Case report: Remission of chronic low back pain and oral dysesthesia comorbid with attention deficit/hyperactivity disorder by treatment with atomoxetine and pramipexole - Kasahara, Satoshi; Kato, Yuichi; Takahashi, Miwako; Matsudaira, Ko; Sato, Naoko; Niwa, Shin-Ichi; Momose, Toshimitsu; Uchida, Kanji (Frontiers in Pain Research, 2023)
Introduction: Oral dysesthesia is a disease characterized by pain and/or abnormal sensations in the oral region, without any organic abnormality. Its symptoms include pain, and it is considered to be a disorder associated with idiopathic oral-facial pain. It is also known that idiopathic oral-facial pain tends to coexist with chronic musculoskeletal pain, including low back pain, even before its onset. Such coexisting idiopathic pain conditions are also called chronic overlapping pain conditions (COPCs). In general, COPCs are often refractory to treatment. Recently, it has been reported that attention deficit hyperactivity disorder (ADHD) is associated with many COPCs, such as pain in the facial and lower back regions and so on. However, there are no reports of 1) ADHD as a comorbidity with oral dysesthesia (OD) or 2) of the therapeutic effects of ADHD medications or dopamine agonists on low back pain and OD or an 3) evaluation of cerebral blood flow over time after treatment with these medications for OD and low back pain. Case Presentation: In this study, we report the case of an 80-year-old man with OD and chronic low back pain that persisted for more than 25 years. His OD and chronic back pain were refractory to standard treatment, prevented him from continuing work, and tended to be exacerbated by conflicts in his relationship with his son. In recent years, ADHD has often been found to be comorbid with chronic pain, and ADHD medications have been reported to improve chronic pain as well. The patient was confirmed to have undiagnosed ADHD and was treated with the ADHD medication atomoxetine and dopamine agonist pramipexole, which dramatically improved his OD, chronic back pain, and cognitive function. Furthermore, along the course of treatment, there was improvement in cerebral blood flow in his prefrontal cortex, which was thought to reflect improved function in the region. Consequently, he was able to resume work and improve his family relationships. Conclusion: Therefore, in the cases of ODs and COPCs, screening for ADHD and, if ADHD is diagnosed, ADHD medications or dopamine agonists may be considered.